Объяснение:
1.
а) 5х²-11х+1=0=121-20=101
√Д=√101
х1 = (11+√101)/10
х2 = (11-√101)/10
б) 5х²-7х+3=0
Д=49-60= -11 - коренів немає
в) 81у²+18у-1=0
Д=324+324=648
√Д=18√2
х1 = (-18+18√2)/162 = (18*(-1+√2))/162 = (-1+√2)/9
х2 = (-1-√2)/9
2.
а) х²+16х+64=0
х1+х2= -16
х1*х2 = 64
х1 = -8
х2= -8
б) х²-17х+30
х1+х2=17
х1*х2=30
х1=2
х2=15
в) х²+9х-22=0
х1+х2= -9
х1*х2= -22
х1=2
х2= -11
г) х²-21х+54=0
х1+х2=21
х1*х2=54
х1=18
х2=3
3.
а) х²+6х-7 = (х - 1)(х + 7)
х²+6х-7=0
Д=36+28=64
√Д=8
х1= (-6+8)/2 = 1
х2= (-6-8)/2 = -7
б) -9х²+12х-4 = -9 * 2/3 = -6
9х²-12х+4=0
-(3х+2)²=0
-3х= -2
х = 2/3
(а-2)(а+2) - 2а(5-а) = (а² - 2²) - 2а * 5 - 2а *(-а) =
= а² - 4 - 10а + 2а² = (а² +2а) - 10а - 4 =
= 3а² -10а - 4
(у-9)² - 3у(у+1) = (у² - 2*у*9 + 9² ) - 3у*у -3у*1 =
= у² - 18у + 81 - 3у² - 3у = (у² - 3у²) - (18у+3у) + 81 =
= - 2у² - 21у + 81
3( х -4)² - 3х² = 3 (х² - 2*х*4 +4²) - 3х² = 3х² - 24х + 48 - 3х² =
= -24х + 48
№2.
25х - х² = 25 * х - х*х = х(25 - х)
2х² - 20ху +50у² = 2(х² - 10ху + 25у²) = 2(х² - 2*х*5у + (5у)² ) =
= 2(х-5у)²
№3.
(с² - b)² - (c²-1)(c² + 1) +2bc² = (c²)² - 2bc² +b² - ( (c²)² - 1²) + 2bc² =
= c⁴ + b² - c⁴ + 1 = b² + 1
при b = - 3 ⇒ (-3)² + 1 = 9 + 1 = 10
№4.
(х - 4)² - 25х² = (х - 4)² - (5х)² = (х-4-5х)(х-4 +5х) = (-4х -4)(6х - 4) =
= -4(х+1) * 2(3х - 2) = - 8(х+1)(3х-2)
a² - b²-4b -4a = (a² - b²) + (-4a -4b) = (a-b)(a+b) - 4(a+b) =
= (a+b)(a-b-4)
№5.
(а+b)² - (a-b)² = 4ab
(a+b +a-b)(a+b -(a-b))= 4ab
2a*(a+b -a+b) = 4ab
2a *2b = 4ab
4ab≡4ab тождество доказано.